Effect of phosphate fertilization and inoculation with VA-mycorrhizal fungi on performance of cassava (Manihot esculenta Crantz) grown on an Alfiso - Kang, B.T.; Islam, R.; Sanders, F.E.; Ayanaba, A. (1980)
Field and greenhouse investigations were carried out in southern Nigeria to study the effects of phosphate fertilization and inoculation with vesicular—arbuscular mycorrhiza on performance of the local cassava (Manihot esculenta Crantz) cultivar Ishinukakijan grown on Egbeda soil series (Oxic Paleustalf). Field-grown cassava appears to have a low P requirement. At 3.4 ppm Bray P-1 or about 0.01 ppm P soil solution tuber yield was still reasonably high at 35 t/ha. Eight ppm Bray P-1 or 0.04 ppm P in the soil solution were required for maximum tuber yield, about 49 t/ha. Sampled at 3 months after planting, a P concentration of above 0.5% and 0.38% in leaf blades and leaf petioles, respectively, were considered adequate. Percentage mycorrhizal fungal infection of cassava fibrous roots depended on extractable soil P levels, being low at high soil P levels and high at low soil P levels. Inoculation with mixed native VA-mycorrhizal fungi or with Glomus mosseae significantly improved growth, lowered P response and increased P uptake in plant tops of pot-grown cassava in sterilized soil. Mycorrhized cassava to utilize phosphorus better from the more available Morocco rock phosphate than one from Togo. Inoculation with Glomus mosseae reduced plant growth and P uptake in unsterilized soil. The results of the pot trials lend support tha the observation that the low P requirement of field-grown cassava may be related to its association with VA-mycorrhizal fungi.